2009
DOI: 10.1038/onc.2008.489
|View full text |Cite
|
Sign up to set email alerts
|

The Tcl1 oncogene defines secondary hair germ cells differentiation at catagen–telogen transition and affects stem-cell marker CD34 expression

Abstract: Overexpression of the TCL1 gene family plays a role in the onset of T-cell leukemias in mice and in humans. The Tcl1 gene is tightly regulated during early embryogenesis in which it participates in embryonic stem (ES)-cells proliferation and during lymphoid differentiation. Here, we provide evidences that Tcl1 is also important in mouse hair follicle (HF) and skin homeostasis. We found that Tcl1 À/À adult mice exhibit hair loss, leading to alopecia with extensive skin lesions. By analysing Tcl1 expression in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
24
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(26 citation statements)
references
References 44 publications
2
24
0
Order By: Relevance
“…For example, the skin of FGF18 conditional knockout mice (K5creFGF18flox) utilizing the Keratin 5 (KRT5) promoter precociously enters anagen via a shortened telogen 14 . Knockout of Tcl1, which is highly expressed in the secondary hair germ and bulge cells during the catagen-telogen transition, results in a loss of the bulge stem cell surface marker CD34 and disturbs HF homeostasis 15 . The role of other molecules in hair cycling were demonstrated by exogenous gene delivery.…”
Section: Basic Biology Of Hair Folliclesmentioning
confidence: 99%
“…For example, the skin of FGF18 conditional knockout mice (K5creFGF18flox) utilizing the Keratin 5 (KRT5) promoter precociously enters anagen via a shortened telogen 14 . Knockout of Tcl1, which is highly expressed in the secondary hair germ and bulge cells during the catagen-telogen transition, results in a loss of the bulge stem cell surface marker CD34 and disturbs HF homeostasis 15 . The role of other molecules in hair cycling were demonstrated by exogenous gene delivery.…”
Section: Basic Biology Of Hair Folliclesmentioning
confidence: 99%
“…It is well known that mTOR activation propagates metastasis and matrix-stimulated cell migration, and treatment with mTOR inhibitors such as rapamycin can block cell motility under numerous experimental conditions (reviewed in [51]). There are also several examples how primary defects of the strictly regulated morphogenic catagen-telogen transition can lead to failed initiation of the ensuing anagen hair cycle, much like that observed in VDR −/− animals [52,53]. Overall, our findings may have uncovered a critical cog—mTOR signaling—in the full understanding of how hair follicles become impaired and degenerate in VDR −/− animals.…”
Section: Discussionmentioning
confidence: 58%
“…In a previous study, poly IC was shown to increase the immunogenicity of human immunodeficiency virus (HIV) VLPs where a high dose of antigen (20 lg) with a high dose of poly IC (50 lg, 100 lg) were used with three immunizations via the intraperitoneal route (18,36). Gardiquimod has demonstrated its efficacy in dendritic cell-based tumor immunotherapy (33,36) in which a high dose of gardiquimod (20 lg) was used. In our study, low doses of antigen (5 lg) and adjuvants (2 lg) were used because a high dose of 10 lg of adjuvant CpG mixed with influenza VLPs caused adverse symptoms after intranasal administration (data not shown).…”
mentioning
confidence: 99%
“…Thus, mimicking the immune stimulating responses of microorganisms, molecular adjuvants based on TLR ligands or agonists have been demonstrated to enhance the immunogenicity of vaccines and are increasingly recognized as key adjuvant targets. As examples, TLR ligands such as monophosphoryl lipid A (MPL), CpG, poly IC, Flagellin, and gardiquimod have been demonstrated to be effective adjuvants when co-administered with vaccine antigens (9,15,18,33,(35)(36)(37). MPL, a TLR4 agonist, has been used extensively in clinical trials as a component in prophylactic and therapeutic vaccines targeting infectious disease (20,23).…”
mentioning
confidence: 99%
See 1 more Smart Citation